HUKUM PRODUK HASIL PERTANIAN DENGAN PUPUK DARI KOTORAN BABI DALAM PERSPEKTIF KRITERIA SISTEM JAMINAN PRODUK HALAL - Ibrahim, Muhammad Yusuf; Masruhen, Mohmed Firdaus Bin (Universitas Mathla’ul Anwar Banten, 2024)
Consumption is an important activity in human life. Therefore, Islam regulates it carefully, from upstream to downstream of the human consumption process. However, in practice, incidents occur that need to be specifically reviewed by Islamic law. Among them is the law on the consumption of agricultural products with fertilizers from pig derivatives such as oil and manure. In addition, consumption standards based on Islamic law have been standardized by the Indonesian government to protect Muslim consumers, known as the halal product guarantee system (SJPH) criteria. So it is necessary to study various aspects of community consumption from upstream to downstream. Therefore, this research aims to analyze the law on agricultural products with fertilizer made from pig manure which is compiled from fatwas and commented critically based on SJPH criteria.